Travel health-related activities and services provided by community pharmacies in Selangor, Malaysia: A cross-sectional analysis. Issue 33 (January 2020) - KC, Bhuvan; Khan, Tahir Mehmood; Xuan, Wong Yin; Alrasheedy, Alian A.; Mohamed Ibrahim, Mohamed Izham; Leggat, Peter A.
Abstract: Background: Millions of tourists visit Malaysia annually while a large number of Malaysians travel overseas. Taking care of travellers' healthcare needs is important aspect of the healthcare system. Community pharmacies are ideally positioned to provide travel health-related services. However, studies are lacking in this area. Therefore, this study aims to explore the nature and type of travel health-related services provided by Malaysian community pharmacies. Methods: A survey was carried out at 135 community pharmacies in nine districts of Selangor, Malaysia, from November 2017 to February 2018, using a self-administered standardized questionnaire. Results: The majority (n = 95, 85%) of community pharmacies reported to have provided services to both international travellers and outbound Malaysian travellers. The common healthcare services provided to international travellers were monitoring of chronic diseases including hypertension and diabetes, and advice on minor ailments, supplements and medical devices. The key health services provided to outbound Malaysian travellers were advice on vaccination requirements, better management of chronic diseases and necessary medications to manage illness during travel. Most of the respondents supported the provision of travel health-related services through the community pharmacies. Conclusion: The study findings showed that Malaysian community pharmacies provided several travel health-related services to both international and Malaysian outbound travellers. Pharmacists in Malaysia are ideally positioned to have an increased role in travel medicine. They have the training to advise on complex medication issues especially with regard to interactions and polypharmacy. However, further training and courses should be provided that are tailored specifically for the needs of this professional group.